Radar absorbing composite structures dispersed with nano-conductive particles. (April 2015) - Choi, Ilbeom; Lee, Dongyoung; Lee, Dai Gil
Abstract: Nano-composites are typically used in radar absorbing structures (RAS) to improve their electromagnetic (EM) wave absorbing performances. The nano-composites are generally composed of E-glass/epoxy composites dispersed with carbonaceous nano-conductive particles such as carbon black and carbon nanotubes (CNT). Because the EM wave absorbing performance of the nano-composite RAS is dependent on the particle concentration of the nano-composites, investigation of its performance with respect to the different nano-composite composition is highly necessary. In this study, the nano-composite RAS were designed using the optimum design method with the various selected nano-composites. The EM wave absorbing performance of the RAS were obtained by numerical simulation with respect to the nano-composites and verified by experimental measurement. Additionally, the effects of the carbonaceous nano-conductive particles on the mechanical properties of the nano-composites were measured. Finally, the optimum nano-composite RAS was suggested considering both electromagnetic and mechanical performances.